ANALYZING THE IMPACT OF THE AUTHORIZED ECONOMIC OPERATOR (AEO) PROGRAM IN INDONESIA - Ikhsanul, Irfan (Unit Penerbitan Politeknik Keuangan Negara STAN, 2024)
This study investigated the impact of the Authorized Economic Operator (AEO) program on imports in Indonesia using the Difference-in-Differences (DiD) methodology with yearly panel data of imports at the firm level. The independent variable represents whether a firm obtains AEO status. The analysis indicates that implementing the AEO program has had a statistically significant and positive effect on imports in Indonesia. Specifically, the findings suggest that the program contributed to a substantial increase in trade volume, likely increasing total import values by 35% and improving overall trade performance. These results underscore the importance of trade facilitation programs, such as AEO, in boosting economic activity and supporting sustainable trade growth. The positive impact observed highlights the potential benefits of expanding the program to include more firms, thereby amplifying its contribution to Indonesia's trade and economic development.